Nanoparticles for neurotrophic factor delivery in nerve guidance conduits for peripheral nerve repair - Escobar, Ane (2022)
Peripheral nerve injuries are a major source of disabilities, and treatment of long nerve gap autografts is the gold standard. However, due to poor availability and donor-site morbidity, research is directed towards the development of regenerative strategies based on the use of artificial nerve guidance conduits (NGCs). Several properties and characteristics of the NGCs can be fine-tuned, such as the architecture of the conduit, the surface topography and the addition of bioactive molecules and cells to speed up nerve regeneration. In this review, US FDA-approved NGCs are described. The recent works, in which polymeric, magnetic, silica-based and lipidic NPs are employed to introduce growth factors (GFs) to NGCs, are overviewed and discussed in depth herein.